Heritability and Gene Effect for Root Characteristics in Peas Measured at Flowering. - Salleh, Ghizan; Gritton, Earl (Springer Verlag, 1994)
Heritability and gene effects for root weight, root volume and root to shoot weight ratio were determined in peas (Pisum sativum L.) at flowering. The populations used were developed from four crosses between lines and cultivars differing in size of the root systems. Broad-sense heritability was between 0.41 and 0.81 for root weight, and between 0.44 and 0.77 for root volume. Additive and dominance effects were important in the genetic control of root and weight volume in all populations, while epistatic effects were important only in two populations. The importance of the genetic parameters in the control of root to shoot weight ratio was unclear. Assuming high correlations between root growth in soil-filled pots in the greenhouse and growth in the field, with the presence of large additive effects and high heritability estimates for root weight and volume, selection for superior pure lines wth large root systems should be effective.